The Effect of Vlog towards Students’ Speaking Skill at the Tenth Grade of SMAN 2 Situbondo: (A Quasi Experimental Study) - Nor Faiseh; Dwi Nur Hadiyansah WS; Nuril Firdaus (International Forum of Researchers and Lecturers, 2025)
This study aimed to analyze the effect of vlog towards students' speaking skills. the method used quasi-experimental. This study was conducted at the tenth grade of SMAN 2 Situbondo. The population was consisted of at least 360 students while the samples were 60 students divided into two classes. 30 students for the experimental class and 30 students for the control class. The sample was selected by purposive sampling. The experimental class was taught using vlog and control class without using vlog. Initially, before treatment, the experimental class's average score of 57.6 and the controlled class's score of 58.66. on the other hand, after following treatments that the experimental class received instruction via video blog had average was 67.73, and their gained score was 10.13., outperformed the control class that did not receive video blog instruction with students' average score being 64.26 and their gained score being 5.6. Besides, the paired t-test indicates that the experimental class scored average was 67.73 higher than the controlled class was 64.27. with a Sig. (2-tailed) (p) of 0.001 and a Sig. Alpha (α) of 0.05. In short, p < (α). It indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Overall, the results indicate that the use of video blogs has a moderate impact on the students’ speaking skill at the tenth grade of SMAN 2 Situbondo.